GEOPOLITICAL GOALS AND GEOSTRATEGY OF UKRAINE - Martsikhiv, K.; Shepelyak, L. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The issues related to the definition of the essence of the concept of "geopolitics" are considered, the geostrategy of Ukraine is studied, and the factors influencing its formation, the main geopolitical goals of Ukraine are characterized. Geostrategy as a practical component of geopolitics is analyzed in detail. The peculiarities of the modern geostrategy of Ukraine are revealed, the main goals used by the states to achieve certain results are given.The main goals and principles of forming the geostrategy of Ukraine are studied and determined, which is an extremely important topic, because in modern conditions a new geopolitical world is emerging, and Ukraine is trying to establish itself in the international arena as an active geopolitical player. The main attention is paid to one of the most important factors that play a significant role in the development of the geopolitical code of any country - the geopolitical position of its territory, the state of the treaty base and relations with other countries, common borders, geopolitical situation in the region and the world. It is noted that the geopolitical position is one of the main determinants that determine the specifics of the geostrategy of any state in geospace. Penetration into the wider world begins with attempts to understand it, establish contacts with it and enter into a multifaceted dialogue. It is emphasized that only then can we find those forms of presentations of our own identity and our own interests in which the world will be able to understand ourselves. Ukraine must realize itself in the geopolitical context and in the context of the development of world civilization. It turns out that the definition of geopolitical interests of Ukraine requires consideration of a complex system of interests of different countries, the distribution of forces - economic, political, military, spiritual - in each of the regions of the world.